The effects of racism and resilience on Black stroke- survivor quality of life: Study protocol and rationale for a mixed-methods approach - Love, Mary F.; Brooks, Andrea Nicole; Cox, Sonya D.; Okpala, Munachi; Cooksey, Gail; Cohen, Audrey Sarah; Sharrief, Anjail Z. (Frontiers in Neurology, 2022)
Introduction: Annual age-adjusted incidence and death rates for stroke are significantly higher among Black Americans than among White Americans. Racism is a significant stressor that contributes to these health disparities for Black stroke survivors (SS). Stress related to stroke, racism, and other psychosocial stressors can negatively impact Black SS quality of life (QoL). Resilience is a dynamic process of positive adaptation to significant stress or adversity. This study aims to examine the effects of experiences of racism and resilience on Black SS QoL during early stroke recovery. Methods and Analyses: This is a prospective observational mixed-methods study. Black or African American community-dwelling adults who have experienced a stroke in the past 8 weeks are eligible for inclusion. Power analysis for a two-tailed linear regression model with α ≤ .05, β .80, an effect size of .15, and a 20% attrition rate resulted in a sample size of 88. Baseline assessments from PhenX Toolkit and other sources will be used to measure experiences of racism, resilience, sociodemographic variables, and psychosocial covariates at participant enrollment. The outcome variable (QoL) will be assessed 6-months post-stroke. Multiple-level linear regression models will be used to test the direct effects of experiences of racism, and the direct and indirect effects of resilience, on QoL. Qualitative data will be collected via small focus groups and analyzed for themes of racism, resilience, and QoL. Discussion: Stroke, a life-threatening stressor that affects both physical and mental health, can negatively impact stroke-survivor QoL. Additionally, Black SS contend with racism-related stress. This context informed how study variables will be measured. For example, experiences of racism will be measured with instruments for both “everyday” discrimination and vigilance. Socio-demographic variables are operationalized to facilitate an accurate assessment of specific social determinants of health that intersect with structural racism, including household income, residential segregation, and access to healthcare. Because of the long-standing history of racism in the US, cultural influences and access to resources are central to the consideration of individual-level resilience in Black SS. Study results may inform the development of interventions to cope with stressors, including racism, that impact Black SS QoL.